Fairness and Frictions: The Impact of Unequal Raises on Quit Behavior - Dube, Arindrajit; Giuliano, Laura; Leonard, Jonathan (American Economic Review, 2019)
We analyze how separations responded to arbitrary differences in own and peer wages at a large US retailer. Regression-discontinuity estimates imply large causal effects of own-wages on separations, and on quits in particular. However, this own-wage response could reflect comparisons either to market wages or to peer wages. Estimates using peer-wage discontinuities show large peer-wage effects and imply the own-wage separation response mostly reflects peer comparisons. The peer effect is driven by comparisons with higher-paid peers—suggesting concerns about fairness. Separations appear fairly insensitive when raises are similar across peers—suggesting search frictions and monopsony are relevant in this low-wage sector. (JEL D63, J31, J42, J62, L81)